A homologue of Nr5a1 activates cyp19a1a transcription additively with Nr5a2 in ovarian follicular cells of the orange-spotted grouper. (15th January 2018) - Shi, Boyang; Lu, Huijie; Zhang, Lihong; Zhang, Weimin
Abstract: Transcription factors of nuclear receptor 5A (Nr5a) subfamily play pivotal roles in regulation of steroidogenic enzymes in vertebrates including teleosts. In the orange-spotted grouper, the expression of Nr5a1a was only detectable in the ovary, spleen, and head kidney in the female. The immunoreactive Nr5a1a was present in ovarian follicular and germ cells. In the ovarian follicular cells surrounding vitellogenic oocytes, Nr5a1a was detected both in the nucleus and cytoplasm, and co-localized with Cyp19a1a and Nr5a2. In the ovarian follicular cells surrounding fully grown oocytes, Nr5a1a was localized almost exclusively to the cytoplasm together with Nr5a2. Nr5a1a could up-regulate cyp19a1a promoter activities through Nr5a sites, and further increase the responses elicited by Nr5a2 at sub-maximal doses. Chromatin immunoprecipitation analysis showed that Nr5a1a bound to cyp19a1a promoter in the vitellogenic but not fully grown ovary. Taken together, Nr5a1a up-regulates cyp19a1a additively with Nr5a2 during vitellogenesis, and its cytoplasmic sequestration may also contribute to the down-regulation of cyp19a1a in the fully grown ovary. Highlights: nr5a1a was only detected in the ovary, spleen, and head kidney in female E. coioides . Immunoreactive Nr5a1a is present in ovarian follicular and germ cells. Nr5a1a co-localizes with Cyp19a1a and Nr5a2 in ovarian follicular cells. Nr5a1a up-regulates cyp19a1a additively with Nr5a2 in vitellogenic ovaries.